Biochar characteristics relate to its utility as an alternative soil inoculum carrier to peat and vermiculite. (February 2015) - Hale, Lauren; Luth, Madeline; Crowley, David
Abstract: Biochar materials have greatly variable physical and chemical properties, which will affect their abilities to serve as carriers for introducing bacteria into soils. Here we examined biochars made from 5 feedstocks produced at 2 highest treatment temperatures (HTT's) by slow pyrolysis. Peat and vermiculite, which are traditional inoculum carriers, and liquid inoculum with no carrier, were included for comparison. All of the carriers were inoculated with a liquid suspension of the plant growth promoting rhizobacterial (PGPR) strain, Enterobacter cloacae UW5, carrying a green fluorescent protein (GFP) marker. Inoculum survival was determined using quantitative PCR to enumerate the GFP markers in DNA extracted from non-sterilized soils directly after incorporation of the inoculated carriers and after a 4-week incubation. The biochars were characterized with respect to carbon and nitrogen content, specific surface area, pH, electrical conductivity, water holding capacity, pore opening diameters, and hydrophobicity to identify specific attributes that influence the survival of the inoculant after introduction into soil. The results indicated that chemical properties of biochar, particularly nitrogen and pH, were among the most important characteristics affecting initial inoculum survival and hence likely the shelf life. However, once incorporated into soil, physical features, including surface area, pore opening diameters, and water-filled pore spaces, were more closely associated with inoculum survival. All biochars tested performed as well as vermiculite and none demonstrated detrimental effects on the UW5 population. The best biochar was that made from pinewood at a HTT of 600 °C (Pine600), which performed as well as peat and sustained higher population densities than vermiculite. The Pine600 biochar was further tested to assess its effect on the expression of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase and auxin synthesis, both of which were unaffected by the presence of biochar at 2% or 5% (w/v) concentrations. Highlights: Inoculum survival was assessed when 10 biochars were used as carriers. Pine600, comparable to peat, sustained higher cell densities than other carriers. Chemical properties of biochar affected initial inoculum survival. Biochar physical features were associated with survival after soil incubation. ACC deaminase activity and auxin synthesis were not negatively impacted by Pine600.